Increasing the Ability of Concentration Through the Implementation of Brain Gym - Septian, Rendra; Darajat, Jajat; Suntoda, Andi; Mulana, Mulana (TEGAR: Journal of Teaching Physical Education in Elementary School, 2018)
The purpose of this study is to improve the ability of concentration. Subjects in this study are the students of grade IV - VI Ciparay Elementary School 07 Kabupaten Bandung Sampling technique in this study is Purposive Sampling with a subject of 42 people. The method used in this study is the experimental method with One-Group Pretest-Posttest Design research. Measuring instrument in this study using Concentration Grid Exercise test. t paired test results. The obtained p-value value 0.00 0.05 Ho rejected, with an increase of 30% then there is the influence of the application of the gym gym to increase the ability of concentration in the students SDN Ciparay 07 Kab. Bandung.Â